Thermally Enhanced Boron Nitride Nanotube/reduced Graphene Oxide Paper and Their Application - Shim, Jaeho; Lee, Jaehyeon; Lee, Joo Song; Son, Dong Ick (KOREAN INST METALS MATERIALS, 2021)
We demonstrated the thermally robust reduced graphene oxide (rGO)/boron nitride nanotube (BNNT) papers and their application in electromagnetic interference shielding. In order to overcome the thermal durability shortcomings of electromagnetic wave shielding paper based on rGO nanomaterial, rGO/BNNT electromagnetic interference (EMI) shielding paper having excellent thermal durability could be manufactured using BNNT nanomaterials having excellent chemical and thermal stability at high temperature. With the addition of a little BNNT, the durability against temperature can be increased by more than two times while there is little reduction in EMI performance.
Keywords: EMI SHIELDING EFFECTIVENESS; COMPOSITES; BNNT; VIBRATION; MATRIX; RGO